Violência escolar e a expectativa de comportamento feminino: percepções de professores/as e diretores/as presentes nos registros de cadernos de ocorrência - Herminio, Ana Beatriz [UNESP] (2014)
The truth is that the violence, in educational institutions, has been one of the biggest concerns and has produced a lot of discussion through the school's actors and education researchers. The ”occurrence book”, becomes a rich material to understand the school routine, its interpersonal relationships and how the teachers and the Board use it to try to ensure discipline and harmony on this environment. In this context, the issue of gender has tightly appeared on school routine either by curricular programme, (that keeps the social standard differences between boys and girls), or by the expectations and the way that teaching institutions expect them to behave. Thus, this research aims to understand school violence with girls as protagonists, according to the reports on occurrences books and the expectation of female behavior by teachers who most register on these books. This research uses:qualitative approach (with stamp in the documentary research), content analysis and took the interviews as an instrument. This, was realized within two public elementary schools cycle II (1and 2) from a city in the countryside of São Paulo and used 22 occurrence books during 2011 and 2012, but kept focus in physical and psychological violence records with girls as protagonists between the 7th and 9th grade. 14 people were interviewed, 4 teachers and 3 members of School Board 1 and 4 teachers and 3 members of School Board 2